Indoor positioning using a-SiC:H technology - Vieira, Manuel (2019)
The nonlinear property of SiC multilayer devices under Ultra Violet (UV) irradiation is used to design an optical processor for indoor positioning. The transducers combine the simultaneous demultiplexing operation with the photodetection and self-amplification. Moreover, we present a way to achieve indoor positioning using the parity bits and the navigation syndrome. A 4 bit representation with the original string colour message and the transmitted 7 bit string, the encoding and decoding accurate positional information processes and the design of SiC navigation syndrome generators are discussed. The visible multilateration method estimates the device's position by using the MUX signal received from several, non-collinear transmitters. The location and motion information is found by mapping position and estimates the location areas.